Needs Analysis of an Integrated Basketball Coaching Policy Model in Indonesia (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
This study analyzed the performance needs of basketball coaching and development policies in Indonesia, focusing on actual performance, expected performance, and performance gaps. Using an explanatory sequential mixed-method design with 35 respondents (teachers, coaches, parents), the study evaluated six variables, including funding support, club-school collaboration, training facilities, competition system, coach development system, and career support. Quantitative data were analyzed using descriptive statistics and the Kruskal-Wallis test, while qualitative data were obtained through interviews. The results showed consistent perceptions across stakeholder groups that actual performance remained suboptimal, while expected performance was high. Performance gaps arose from limited funding, weak collaboration, inadequate facilities. There was no established competition system, coach development system, or clear career support. The findings provide an empirical foundation for formulating a more integrated basketball coaching and development policy model.